2017
DOI: 10.1590/1980-5373-mr-2017-0126
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bleached Jute Fiber Filler on the Properties of Vulcanized Natural Rubber

Abstract: There is growing interest in replacing the synthetic reinforcements used for natural rubber (NR) composites with natural fibers from renewable, environmentally sustainable sources. Jute fibers may be suitable reinforcements for NR because they have a high tensile strength, which is comparable to other fillers such as glass fibers. Thus, we studied the incorporation of bleached jute fibers into NR, characterizing the mechanical, dynamic mechanical, and morphological properties of the composites. The addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The SEM image of the tensile fractured sample of NR-CNF 4 phr composite ( Figure 7E) shows voids and fiber pullouts. These voids act as centers for crack propagation, which will ultimately result in inferior mechanical properties [50].…”
Section: Fractographic Studies Of Nr-cnf Nanocompositesmentioning
confidence: 99%
“…The SEM image of the tensile fractured sample of NR-CNF 4 phr composite ( Figure 7E) shows voids and fiber pullouts. These voids act as centers for crack propagation, which will ultimately result in inferior mechanical properties [50].…”
Section: Fractographic Studies Of Nr-cnf Nanocompositesmentioning
confidence: 99%
“…That implies the linear model might not be the right model to describe our data. Also, we found many articles showing a significant tan δ peak value decrease after adding bioadditives in a single polymer matrix although the relationship is not discussed further [27]. This indicates that the logarithm model provides a better fit (Figure 7).…”
Section: Resultsmentioning
confidence: 90%
“…Correia et al 26 reported bleaching treatment for the surface modification of jute fibers (JFs). In this process, bleaching treatment was performed by using sodium chlorite and glacial acetic acid as bleaching agents.…”
Section: Surface Modification Methods Of Natural Fibersmentioning
confidence: 99%